Acanthophyllia deshayesiana (Michelin, 1850) Coral Species Is Not Synonym With Cynarina lacrymalis (Milne Edwards & Haime, 1848) - Robba Fahrisy Darus; Neviaty Putri Zamani; Suharsono Suharsono; Dedy Duryadi Solihin (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2016)
Acanthophyllia deshayesiana has a different habitat with Cynarina lacrymalis in the nature, but they have same character on living forms, diameter, and height of corallite. Both of these species are considered synonym, thus it needs verification study to describe whether it is synonym species or not based on morphological data. Eleven descriptive characters and seven morphometric characters were used to verify the synonym species of these coral. Descriptive data were performed by scoring method, while morphometric data were obtained from morphometric. Morphometric data were analyzed by Correspondence Analysis of Principal Coordinates (CAP) and Agglomerative Hierarchical Cluster (AHC), while descriptive data were analyzed by UPGMA (Unweight Pair Group Method with Arithmetic Mean). The result showed that both of these coral cannot differentiate based on morphometric measurement. It can differentiate significantly based on descriptive characters, so both of these coral are not synonym. Keywords: synonym, morphometric, descriptive, Cynarina lacrymalis, Acanthophyllia deshayesiana